Kompetensi Supervisi Kepala Sekolah Dalam Meningkatkan Kinerja Mengajar Mengajar Guru - Agus Ruhimat (LPPM Politeknik Pratama, 2023)
The objective of the research is to describe of academic supervision in improving the teachers’ performance of Public Elementary school 6 Ketahun North Bengkulu. The method of this research was descriptive qualitative method. The data collecting technique used interview, observation and documentation. The data analysis technique was done by reducing the data, presenting the data, and drawing conclusion. The results of this research showed that (1) planning of academic supervision was by coordinating with senior teachers; (2) implementating of academic supervision was done by visiting class and observation; (3) monitoring was done by pre- visiting class and post visiting class.